PERAN PENDAPATAN PAJAK BUMI DAN BANGUNAN (PBB) DALAM MENDUKUNG PEMBANGUNAN DAERAH DAN PENYELENGGARAAN PELAYANAN PUBLIK: KAJIAN PUSTAKA ATAS KEBIJAKAN PENGALIHAN KEWENANGAN DAN OPTIMALISASI PAD INDONESIA - Loso Judijanto (ADMIN: Jurnal Administrasi Negara, 2026)
This article discusses the strategic role of Rural and Urban Land and Building Tax (PBB-P2) in strengthening Local Own-Source Revenue (PAD) to support regional development and public services after the transfer of authority from the central government to the regions through Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD). The research method used was a literature review. The results show that the transfer of authority increased the contribution of PBB to PAD by 15-25% in urban areas such as DKI Jakarta, although regional disparities and administrative challenges such as low collection effectiveness (60-70%) still hamper rural areas. Optimisation through GIS-based SPPT digitalisation, PTSL data synchronisation, and taxpayer socialisation has proven effective in encouraging PAD allocation for basic infrastructure, health, education, and public services, in line with SDGs 9 and 11. This study recommends reforming Bapenda human resources, integrating national technology, and implementing progressive incentives to maximise sustainable fiscal benefits for the Indonesia Emas 2045 vision.